2014
DOI: 10.1371/journal.pone.0110851
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan Potentiates Epithelial-To-Mesenchymal Transition in Anoikis-Resistant Human Lung Cancer Cells

Abstract: Alteration of cancer cell toward mesenchymal phenotype has been shown to potentiate tumor aggressiveness by increasing cancer cell metastasis. Herein, we report the effect of triclosan, a widely used antibacterial agent found in many daily products, in enhancing the epithelial-to-mesenchymal transition (EMT) in aggressive anoikis resistant human H460 lung cancer cells. EMT has been long known to increase abilities of the cells to increase migration, invasion, and survival in circulating system. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Commonly used in personal care products, triclosan and BPA ( 456 ), are endocrine disruptors ( 457–459 ) that are often detected in waters downstream in urban areas ( 460 , 461 ). In addition to immune evasion mechanisms ( 36 , 142 , 145 ), they interfere with wide spectrum of cancer-related mechanisms ( 36 , 173 , 429 , 462–464 ). DEHP ( 472 ) is also an endocrine disruptor ( 466 , 467 ) that can impact multiple hallmarks such as immune evasion, resistance to cell death, evasion of antiproliferative signaling, sustained proliferative signaling and tumor-promoting inflammation ( 36 , 288 , 468 , 469 ).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly used in personal care products, triclosan and BPA ( 456 ), are endocrine disruptors ( 457–459 ) that are often detected in waters downstream in urban areas ( 460 , 461 ). In addition to immune evasion mechanisms ( 36 , 142 , 145 ), they interfere with wide spectrum of cancer-related mechanisms ( 36 , 173 , 429 , 462–464 ). DEHP ( 472 ) is also an endocrine disruptor ( 466 , 467 ) that can impact multiple hallmarks such as immune evasion, resistance to cell death, evasion of antiproliferative signaling, sustained proliferative signaling and tumor-promoting inflammation ( 36 , 288 , 468 , 469 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, indicators like the switching between E-cadherin and N-cadherin, as well as EMT transcription factors snail and slug are more acceptable as hallmarks of EMT [ 2 5 ]. In particular, lung cancer H460 cells were shown to undergo EMT in response to various stimuli [ 33 , 34 ]. EMT features of H460 cells were characterized by (i) the change of cell morphology from epithelial to fibroblast-liked mesenchymal shape, (ii) the increased EMT markers N-cadherin, vimentin, snail, and slug, together with the reduction of epithelial marker E-cadherin, and (iii) EMT behaviors, including increased migration, invasion and tumorigenic potential [ 33 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCS elevated proinflammatory cytokine expression of TNF-α and IL-6 in mouse liver (Yueh et al 2014). Many other in vitro studies suggested that TCS promotes cancer (Kim et al 2014; Lee et al 2014; Winitthana et al 2014; Wu et al 2015). Conversely, in other studies, investigators provided data suggesting that TCS may inhibit cancer development (Sadowski et al 2014; Deepa et al 2012; Schmid et al 2005).…”
Section: Triclosan-mediated Adverse Health Effectsmentioning
confidence: 99%